2018
DOI: 10.1186/s13223-018-0279-0
|View full text |Cite
|
Sign up to set email alerts
|

Asthma

Abstract: Asthma is the most common respiratory disorder in Canada. Despite significant improvement in the diagnosis and management of this disorder, the majority of Canadians with asthma remain poorly controlled. In most patients, however, control can be achieved through the use of avoidance measures and appropriate pharmacological interventions. Inhaled corticosteroids (ICS) represent the standard of care for the majority of patients. Combination ICS/long-acting beta2-agonist inhalers are preferred for most adults who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(93 citation statements)
references
References 30 publications
1
87
0
5
Order By: Relevance
“…Studies on six or more separate populations revealed that asthma is associated with various genes, such as CTLA4, GSTM1, IL4R, IL10, LTC4S, and SPINK5 [156], many of which are related to the immune system or inflammation. Although symptoms can be prevented by avoiding allergens and irritants, and by the use of inhaled corticosteroids, there is no cure for asthma [157].…”
Section: Respiratory Inflammationmentioning
confidence: 99%
“…Studies on six or more separate populations revealed that asthma is associated with various genes, such as CTLA4, GSTM1, IL4R, IL10, LTC4S, and SPINK5 [156], many of which are related to the immune system or inflammation. Although symptoms can be prevented by avoiding allergens and irritants, and by the use of inhaled corticosteroids, there is no cure for asthma [157].…”
Section: Respiratory Inflammationmentioning
confidence: 99%
“…8 Por otra parte, el perfil Th1 (IFN-γ, interferón gamma) activa fagocitos, producción de opsoninas y estimula la respuesta inmune celular. 9 Los componentes liberados por ambos perfiles producen broncoconstricción, inflamación y engrosamiento del músculo liso.…”
Section: Antecedentesunclassified
“…Asthma is a widespread disease affecting 300 million people around the world and estimations predict that 100 million more will be affected by 2050 [ 1 ]. It is characterized by airway hyper-responsiveness, narrowing of the airways, inflammatory cell recruitment, and increased mucus production [ 2 ]. Further, allergic asthma is characterized by an allergen-triggered eosinophilic infiltration; the presence of type 2 cytokines such as interleukin (IL)-4, IL-5, and IL-13; and the presence of Immunoglobulin IgE [ 2 ].…”
Section: Introductionmentioning
confidence: 99%